IMPROVING STUDENTS’ READING COMPREHENSION BY USING NUMBERED HEADS TOGETHER (NHT) TECHNIQUE - Vivi Liana (Language and Education Journal, 2018)
Reading is important subject that should be taught. NHT is one of the techniques that can be used to improve students' reading comprehension. The main purpose of this study was to find out whether or not there was any significant difference in students' reading achievement between students who were taught by using (NHT) technique and that of those who were not. The experimental method was used to conduct the study. The sample was taken by using purposive sampling method which consisted 32 in each group. To select the experimental and control groups, a flip coin was used. Therefore, class VIII 3 was the experimental group whereas VIII 4 as the control group. Multiple choice was used to collect the data. The data obtained were analyzed by the ttest The value of t-obtained was 3.280, at the significant level p<0.05 in two-tailed testing with df = 62, the critical value of t-table = 1.999. Since the value of t-obtained was higher than t-table, the null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. It meant that there was a significant difference in students' reading achievement between the students who were taught by using (NHT) technique an